Availability and amendment of phosphorus level in a soil of the Submedium São Francisco region in relation to buffel grass yield - Faria, Clementino Marcos B. de; Albuquerque, Severino G. de (Pesquisa Agropecuaria Brasileira, 2014)
The relationship between phosphorus levels in the soil and buffel grass (Cenchrus ciliaris L.) dry matter production was studied in a Plinthic Podzolic soil of the Submedium São Francisco River region. The different levels were produced by adding increasing amounts of phosphorus to the soil. According to the relative yields of the grass, the levels of phosphorus were classified as: very low, P up to 3.5 ppm; low, P from 3.6 ppm to 6.5 ppm, and from 3.6 ppm to 6.8 ppm; medium, P from 6.6 ppm to 10.5 ppm and from 6.9 ppm to 10.0 ppm; high, P from 10.6 ppm to 20 ppm, and from 10.1 ppm to 17.7 ppm; and very high, P superior to 20 ppm and 17.7 ppm, determined by the Mehlich and Bray 1 methods, respectively. Amounts of phosphorus necessary to amend the soil in each of the five levels in the order indicated above, would be: 200, 150, 120, 50 and 0 kg/ha of P2O5. The total amount of phosphorus taken up by the grass corresponded to 24.9 kg/ha/year of P2O5, at the maximum dry matter yield (8,700 kg/ha).
Keywords: phosphorus fertilization; analysis method; critical level; plant phosphorus; Cenchrus ciliaris